Transition Challengs From 4.0 To 5.0 Era: A Systematic Review On Education Perspective - Ni Made Anggi Arlina Putri (IAHN-TP Palangka Raya, 2022)
The rapid growth of science and technology impact on all human lines including educational. The revolution era 4.0 is considered as a time of technology empower all aspects of society in which degreed humanists. The new society concept is born in order to balancing the application of technology in daily life without reducing human role. However, the new paradigm always brings its obstacles. For example, in education field, the teaching learning process faced several challenging than the previous one. Therefore, this study aims to determine the transition challenges from revolution era 4.0 to Society 5.0 viewed from educational perspective. The systematic review approach is adopted in order to describing the educational challenges due to that transition. The findings suggest to strengthen the conceptual theories and also become the basic of application education 5.0 era.